Mandatory Bequest for Non-Muslim Heirs in Indonesian Islamic Inheritance Law - Akmal Yandi; M. Hidayat Ediz; jurna Petri Rozi; Ruqayyah Mustafa Mahmud Abdullah Hasan (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
Article 171 of the Compilation of Islamic Law (Kompilasi Hukum Islam / KHI) stipulates that heirs must be Muslim and related through blood or marriage. Nevertheless, Decision No. 04/Pdt.P/2013/PA Bandung granted inheritance rights to non-Muslim heirs through the mechanism of wasiat wajibah (mandatory bequest). This decision has generated scholarly debate because the majority of Islamic jurists consider religious difference a legal impediment to inheritance, as reflected in prophetic traditions. This study aims to analyze the judges’ legal reasoning (ratio decidendi) and examine its compatibility with the principles of Islamic inheritance law and Indonesian positive law. Employing a qualitative method with a normative juridical approach, this study analyzes statutory regulations, fiqh literature, and judicial decisions. The findings reveal that the judges adopted an interpretive approach by referring to minority juristic opinions and the concept of wasiat wajibah to accommodate substantive justice within Indonesia’s pluralistic society. However, the decision also raises legal concerns regarding the jurisdictional authority of the Religious Court and its consistency with the fundamental principles of Islamic inheritance law concerning religious difference as a barrier to inheritance.